Positive Psychology and Happiness: A New Intervention for College Students - Moch Bahrudin; Tanty Wulan Dari; Siti Maimuna (Research Psychologie, Orientation et Conseil, 2024)
The mental health and well-being of college students have become critical concerns, with rising levels of stress, anxiety, and depression reported globally. Traditional mental health interventions often focus on symptom reduction, but positive psychology emphasizes enhancing happiness and personal strengths. This study evaluates the effectiveness of a positive psychology intervention on the well-being of college students. A total of 200 students participated, with 100 assigned to the experimental group and 100 to the control group. The experimental group underwent an 8-week intervention involving gratitude exercises, strengths identification, and mindfulness practices, while the control group received no intervention. Data were collected using the Positive and Negative Affect Schedule (PANAS), the Satisfaction with Life Scale (SWLS), and the State-Trait Anxiety Inventory (STAI) before and after the intervention. Results showed significant increases in positive affect and life satisfaction, alongside reductions in anxiety and stress in the experimental group compared to the control group. Qualitative feedback indicated improvements in optimism and resilience. The study concludes that positive psychology interventions can effectively enhance happiness and well-being among college students, suggesting the potential for incorporating these interventions into college mental health programs to promote healthier lifestyles.